Shape dynamics : relativity and relationalism - Mercati, Flavio (Oxford University Press, 2018)
Shape Dynamics is a radical yet soundly based reinterpretation of Einstein's theory of gravity that has opened up new approaches to gravity research. This text offers both a brief introduction and a detailed walk-through of the motivations for the theory, its development from first principles and an in-depth look at its present status.
Keywords: Relativity (Physics); Gravitation.; Astrodynamics.; Gravitation; Relativité (Physique); Astrodynamique.; TECHNOLOGY & ENGINEERING -- Engineering (General); Astrodynamics; Electronic books.